Mortal engines : a novel - Reeve, Philip (New York : HarperCollins, 2003)
In the distant future, when cities move about and consume smaller towns, a fifteen-year-old apprentice is pushed out of London by the man he most admires and must seek answers in the perilous Out-Country, aided by one girl and the memory of another.
Part 1: The hunting ground -- Valentine -- The waste chute -- The out-country -- The Lord Mayor -- Speedwell -- High London -- The trading center -- The Jenny Haniver -- The 13th Floor Elevator -- Airhaven -- The gasbag and gondola -- The resurrected man -- The guildhall -- The Rustwater Marshes -- The turd tanks -- The pirate suburb -- Bevis -- The Sea of Khazak -- The Black Island -- In the engineerium -- Grike -- MEDUSA -- Part 2: An agent of the league -- The historians -- Batmunkh Gompa -- Dr. Arkengarth remembers -- A stranger in the mountains of heaven -- Going home -- A hero's welcome -- The eavesdropper -- Chudleigh Pomeroy sees it through -- Wine and nibbles and the dawn of a new era -- Idea for a fireworks display -- The cathedral -- The shadow of bones -- The bird roads.
Accelerated Reader/Renaissance Learning
Keywords: London (England) -- Fiction; Science fiction; Steampunk fiction; Young adult fiction; Science fiction -- Juvenile; Steampunk fiction -- Juvenile